Structural and Colloid Effects of Interaction between Shungite Carbon Nanoparticles and Linoleic Fatty Acid - Goryunov, Ц#144;. S.; Borisova, Ц#144;. G.; Rozhkov, S. S.; Rozhkova, N. N. (Current Nanoscience, 2023)
Background: The effect of bionanointeractions on graphene-biomolecule nanohybrids is of great interest, since external influences on their structural and surface properties can significantly affect their biological activity. Introduction: The effects of the fatty acid binding with shungite carbon (ShC) nanoparticles on the stability of aqueous dispersions of ShC and the oxidation state of ShC (oxygen-containing groups) were studied using linoleic acid (LA) as an example. Methods: The size and surface charge (ζ -potential) of the ShC-LA associates formed at various LA concentrations in the dispersion were estimated using the dynamic light scattering method and the ultraviolet (UV) absorption spectra of dispersions were taken. Results: The negative ShC charge becomes less negative upon LA binding, depending on LA concentration. The size of ShC upon functionalization by LA molecules does not depend on LA concentration, suggesting the predominance of surface rearrangement of NPs, rather than a change in their global structure. ShC - LA interaction is accompanied by an increase in absorption in the UV spectrum region of conjugated С=С bonds, the reduction of С=Ц#158; groups, sp2 hybridization and bonds in the plane of graphene fragments, the basic structural units of ShC. Conclusion: The results are interpreted in terms of the surface structural effects of LA on ShC that affect variations of the colloid and redox characteristics of ShC in aqueous dispersion.
Keywords: linoleic acid